The role of high-dose intravenous methylprednisolone in the treatment of varicella associated thrombocytopenic purpura - Aji, Dolly Yafet; Altınkaya, Nüvit; Güler, Ayşe; Ayhan, Yusuf İzzet and Erginel, Ayten and Cenani, Asım (The Turkish Journal of Pediatrics, 1993)
Two children with varicella associated thrombocytopenia are presented. Case 1, evidencing no mucosal or parenchymal bleeding was administered prednisone 2 mg/kg/day therapy after having been put under observation for a period of one week without medical treatment. There was an increase in the platelet count during the period of therapy culminating in a return to normal on the eighth day. Case 2, who was in poor clinical condition at presentation, was treated with high-dose intravenous methylprednisolone (HIVMP) 30 mg/kg/day, resulting in the platelet count returning to a normal level (180,000/mm³) on the second day of therapy. HIVMP therapy is recommended in the treatment of life-threatening cases of thrombocytopenia because of its rapid action, limited side-effects, and its low cost.